Pelatihan Pemanfaatan Learning Management System (LMS) “SIAJAR” untuk Pemelajaran Daring Terintegrasi dan Terkendali - Ahmad Saeroji; Muhsin Muhsin; Dian Fithra Permana (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2022)
The COVID-19 pandemic has had the impact of disrupting education with a new normal. The implementation of learning activities is optimized online with synchronous (virtual face-to-face) and asynchronous (self-directed learning and collaborative learning) learning. However, a number of teachers experience problems when carrying out learning, especially in the use of an integrated Learning Management System (LMS). The implementation of the service is carried out with a webinar model through the zoom application. The result of the service activity is that Economics teachers who are members of the Economics MGMP of SMA Kebumen Regency are able to create an account at SiAjar and are able to design learning with the SIAJAR LMS. The method used for the implementation of the service is online mode because the conditions for the spread of covid have not subsided. The activity begins with account creation, material creation, assignments, discussions and assessments at LMS.